Embryonic and post-embryonic lethals induced by diethyl sulfate in mature sperm of Drosophila melanogaster - Muñoz, Enzo R.; Mazar Barnett, Beatriz (Elsevier/North-Holland Biomedical Press, 1978)
Fil: Mayo, José Comisión Nacional de Energía Atómica; Argentina